Jatropha curcas L. Root Structure and Growth in Diverse Soils - Ofelia Andrea Valdés-Rodríguez; Odilón Sánchez-Sánchez; Arturo Pérez-Vázquez; Joshua S. Caplan; Frédéric Danjon (The Scientific World Journal)
Unlike most biofuel species, Jatropha curcas has promise for use in marginal lands, but it may serve an additional role by stabilizing soils. We evaluated the growth and structural responsiveness of young J. curcas plants to diverse soil conditions. Soils included a sand, a sandy-loam, and a clay-loam from eastern Mexico. Growth and structural parameters were analyzed for shoots and roots, although the focus was the plasticity of the primary root system architecture (the taproot and four lateral roots). The sandy soil reduced the growth of both shoot and root systems significantly more than sandy-loam or clay-loam soils; there was particularly high plasticity in root and shoot thickness, as well as shoot length. However, the architecture of the primary root system did not vary with soil type; the departure of the primary root system from an index of perfect symmetry was 14±5% (mean ± standard deviation). Although J. curcas developed more extensively in the sandy-loam and clay-loam soils than in sandy soil, it maintained a consistent root to shoot ratio and root system architecture across all types of soil. This strong genetic determination would make the species useful for soil stabilization purposes, even while being cultivated primarily for seed oil.